Android-based Mobile Multimedia Application Development Training - Jafar Shadiq; Intan Dwi Fatmaningtyas; Dwi Ismiyana Putri; Ahmad Safei; Rayhan Wahyudin Ratu Lolly (STMIK Pontianak, 2021)
Covid-19 demands the use of technology as an online learning media tool. The technology that becomes a low-cost developer is the Android Technology operating system. The main target of this community service activity is the 3rd & 5th semester Computer System Study Program students at the Faculty of Science and Technology at the Panca Budi Development University in using Android technology, where learning about Android has been carried out but not maximized in building a Mobile Application. The method used is to provide training and demonstrations in making Multimedia Applications using Android Studio with online media support in the form of Zoom, YouTube, and Google Drive links. The results of the feedback response to material questions submitted by the resource person were 67% very good, participant responses to the material presented were 41% good, the relationship between material and participant needs was 59% very good, the relationship between material and applications that could be absorbed by participants was 54% very good, the linkage of the material with needs is 42% good, the presentation technique of the presenter is 56% very good, the time spent by the presenter is 44% giving a good response, the clarity of the material is 59% clear, the interest of the participants is 47% good, and overall satisfaction level of 51% gave a satisfied response to the training activities.